(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: It is observed that the morphologic and morphometric variability of the occipital bone structures may coexist in the same individual or among different subjects of the same or different populations and thus, a sound knowledge of the morphometry of this area can provide important benefits in determining safe surgical zones during surgical procedures. Aim: The present study was aimed at measuring the length (right and left) and width (right and left) of the hypoglossal canal among adult dry skulls of two states in southern Nigeria. Materials and Method: This study adopted the cross sectional study design. A total of eighty (80) hypoglossal canal; right and left were selected by simple random sampling and their length and width were measured with the aid of the digital vernier caliper. Results: The hypoglossal canal length on the right side was seen to be higher compared to the left length of the hypoglossal canal while the right hypoglossal canal width was seen to be higher compared to the left hypoglossal canal width and also observed differences between the right and left sides were statistically significant (P=0.01). Conclusion: There was a statistical significant difference with regard to hypoglossal canal length (right and left) and width (right and left) among the studied population. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.670-672